Comparative evaluation of post-operative pain after pulpectomy with k-files, kedo-s files and mtwo files in deciduous molars -a randomized clinical trial - Nair, Manisha; Jeevanandan, Ganesh; R, Vignesh; EMG, Subramanian (Brazilian Dental Science, 2018)
Objective: Despite the tortuous course of primary root canal system, a paradigm shift occurred from conventional hand files to rotary system, which lead to faster, cost-effective, uniform and predictable fillings. One of the many advantages being, reduction in post-operative pain with the use of rotary system. Many rotary file systems were introduced, with the recent one, the Kedo-S. So the present study aimed to compare and evaluate the post – operative pain after pulpectomy using K-files, MTwo files and Kedo-S files in deciduous molars. Material and Methods: 75 teeth were randomly divided into three groups (group A – K-files, group B - Kedo-S files and group C - MTwo files) for pulpectomy of primary molars. Post – operative pain was assessed every 6,12,24,48 and 72 hours using facial pain scale. Results: 44% of volunteers in K-file group had moderate pain followed by Kedo-S group that is 8% and then MTwo files that is 4%. Conclusion:  The least post-operative pain was found in Mtwo group followed by Kedo-S group and K-file group.KeywordsPulpectomy; Post-operative pain; MTwo; Kedo-S.